FORMATION OF CREATIVE ACTIVITY OF STUDENTS IN THE SYSTEM STUDY OF MUSIC CYCLE SUBJECTS (Pedagogy of Higher and Secondary Education, 2003)
The peculiarity ofstudents *creative activity while studying series of musical subjects is examined in the article. The notions “activity ”, “creative activity ”, “musical creation ” and role of improvisation and creative interpretation of musical compositions are exposed in the article as methods of formation a creative personality;
Keywords: 1